The effectiveness of adjunct music therapy for patients with schizophrenia: A meta‐analysis. (November 2020) - Jia, Ruiying; Liang, Dandan; Yu, Jingfen; Lu, Guangli; Wang, Zihui; Wu, Zhen; Huang, Haitao; Chen, Chaoran
Highlights: This is the latest meta-analysis reporting the effect of music therapy in schizophrenia. Adjunct music therapy is a promising treatment for schizophrenia. The long-term effects of music therapy in schizophrenia need further investigation. Abstract: To evaluate the efficacy of adjunct music therapy on patients with schizophrenia, we conducted a meta-analysis of currently available randomized controlled trials and controlled clinical trials. Eight electronic databases (CNKI, PubMed, EMBASE, Cochrane Library, PsycINFO, Web of Science, Psychology and behavioural Sciences Collection, and Medline) were systematically searched from inception to January 2020. Standard mean difference (SMD) with 95% confidence interval (CI) values were used to evaluate the effects of music therapy. Finally, we selected eighteen studies comprising 1, 212 participants comparing with control conditions. The meta-analysis demonstrated that adjunct music therapy significantly improved total symptoms (SMD = -0.48, 95%CI: -0.74 to -0.22), negative symptoms (SMD=-0.56, 95%CI: -0.72 to -0.40), depression symptoms (SMD = -0.35, 95% CI: -0.54 to -0.17), and quality of life (SMD = 0.35, 95%CI: 0.07 to 0.62) in people with schizophrenia compared with the control group. In addition, the meta-analysis indicated no publication bias for total symptoms, negative symptoms, and positive symptoms. The sensitivity analysis showed that the result was reliable. But the quality of evidence is still low, more well-designed studies with larger sample size and high quality are needed to confirm the efficiency of adjunct music therapy in treating schizophrenia.